Responses of Madrasah toward Social Changes in Aceh Society - Inayatillah Inayatillah (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This article discusses about how madrasahs respond the social changes occurred in Aceh society. Why do, nowadays, Acehnese parents are more interested to send their children to madrassahs? This research therefore aims to reveal any endeavors made by madrasah as responses toward changes in Aceh society and to find out any driving factors that may influence Aceh society to send their children to madrasahs. This study indicates that any changes occurred during the early emergence of madrasahs are mainly caused by sociopolitical and religious circumstances. Furthermore, the dynamic of post-independence madrasahs is mainly affected by government’s policy. Changes occurred in madrasahs during next periods began to indicate an increasing quality of its education service as the result of regional autonomy and the implementation of Islamic sharia. As the implication, the autonomy of education is now conducting quality-oriented education, relevant with current global situation and corresponds with local needs. To attain this goals, government implement school/madrasahs-based management concept (MBS). This MBS concept gave opportunity for each madrasahs to improve and initiate featured programs that corresponds with local needs. This is one of many factors that increase society’s interest toward madrasahs, aside from Islamic education available in madrasahs. Keywords: madrasah, social changes, Aceh